Tech-Driven Lifelong Learning: Enhancing Oral Communication Through HelloTalk’s Interactive Features - Nurbani, Nungki; Nurbani, Armelia Nungki (E-Link Journal, 2025)
Mastering English communication skills is essential in today's globalized world, yet Indonesian students often struggle due to limited authentic practice and reliance on traditional, less interactive methods. This study investigates the use of HelloTalk, a mobile-assisted language learning (MALL) application, to address these challenges by enhancing oral communication skills among English Education students. Specifically, it examines how HelloTalk bridges the gap in real-world language practice while identifying its limitations and proposing solutions. A qualitative case study was conducted, involving semi-structured interviews with six third-semester students taking a Professional Listening and Speaking course at a private university in Surabaya. The results indicate that HelloTalk effectively improves speaking fluency, vocabulary retention, and cross-cultural communication through direct interaction with native speakers. However, key challenges emerged, including difficulties in finding compatible language partners, the lack of message-editing features leading to communication errors, and the app’s high storage consumption. To mitigate these issues, the study proposes a blended learning approach that combines HelloTalk’s interactive strengths with structured classroom instruction, such as targeted grammar exercises and vocabulary drills to create a more balanced and effective learning experience. This integration ensures students benefit from both authentic practice and systematic skill development. The findings highlight the need for technical improvements to HelloTalk and underscore the importance of combining digital tools with traditional pedagogy.